Using measures of specific abilities to predict training performance in Canadian Forces operator occupations. - Campbell SK; Catano VM (Military Psychology, 2004)
This study examined the predictive validity of information processing measures-Speed of Closure, Flexibility of Closure, Perceptual Speed, and Auditory Attention-on training performance. The incremental validity of these validity measures beyond general cognitive ability was examined in a military sample of Canadian Forces personnel in the Operator Family. Trainees engaged in Qualification Level 3 training (n = 122) completed 5 information processing ability measures, the Canadian Forces General Classification Test Form 3 Revised (n = 72), and the Canadian Forces Aptitude Test (n = 98). The criterion was a global percentage grade taken from course evaluation reports. Information processing improved the predictive validity of selection against training performance when used with measures of general cognitive ability DeltaR2 = .06). The only specific ability measure that significantly predicted training performance was the X-A2 battery, a measure of auditory attention beta = .21, p < .05). The information processing measures did not reach significance but still contributed to the predictive equation. These results are comparable with past research where specific abilities provided small yet statistically significant increases in incremental validity beyond g.